Tsunami to survive from tsunami - Murata, Susumu; Imamura, Fumihiko; Katoh, Kazumasa; Kawata, Yoshiaki; Takahashi, Shigeo; Takayama, Tomotsuka (Advanced series on ocean engineering, 2018)
"The book is organized into two parts: the first part covers (i) the precious lessons obtained from recent actual tsunami disasters including the 2004 Indian Ocean Tsunami and 2011 Great East Japan Earthquake Disaster, (ii) fundamental knowledge of tsunami for our survival, and (iii) concludes the lessons learnt and listing measures for tsunami disaster mitigation for saving human lives. The second part presents tsunami from academic perspective in two chapters: one describes tsunami occurrence mechanism and near-shore behavior; the other mentions numerical simulation and forecasting of tsunami."-- Publisher's website